Implementasi Layanan Inklusif Anak Berkebutuhan Khusus Tunarungu di SLB Widi Asih - Ine Apriani; Sandri Dayani; Sri Wahyuni; Syaripah Aliyah (Edu Happiness : Jurnal Ilmiah Perkembangan Anak Usia Dini, 2023)
This study aims to describe the implementation of inclusion services for children with special needs for the deaf at the Widi Asih Special School. The research method used is descriptive analysis method with a qualitative approach. The results of the study show that the implementation of inclusion services for children with special needs at SLBN Widi Asih is carried out through a special program, namely by developing praga media communication such as letter cards, posters, media pictures and using sign language for deaf children so they can participate in learning at school. Our findings also found that this special program can minimize deaf children experiencing learning delays. Because basically the obstacles that occur in deaf children make it difficult to speak, so that their visual and intellectual senses are used as a complement to hearing loss.